1992
DOI: 10.1063/1.860313
|View full text |Cite
|
Sign up to set email alerts
|

Ion heating and magnetohydrodynamic dynamo fluctuations in the reversed-field pinch

Abstract: Ion temperatures have been measured in the Madison Symmetric Torus (MST) [Dexter et aL, Fusion Technol. 19, 131 ( 199 1 j] reversed-field pinch (RFP) with a five channel charge exchange analyzer. The characteristic anomalously high ion temperature of RFP discharges has been observed in the MST. The ion heating expected from ion-electron collisions is calculated and shown to be too small to explain the measured ion temperatures. The charge exchange determined ion temperature is also compared to measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 17 publications
2
52
0
Order By: Relevance
“…In the Earth's magnetosphere, reconnection is believed to occur in the day-side magnetopause and in the magnetotail, where charged particles can be accelerated along field lines toward the polar regions, giving rise to the aurora [5]. In laboratory plasmas such as reverse-field pinches, enhanced ion heating has been seen to correlate with magnetic fluctuations associated with reconnection and dynamo activity [6].…”
mentioning
confidence: 99%
“…In the Earth's magnetosphere, reconnection is believed to occur in the day-side magnetopause and in the magnetotail, where charged particles can be accelerated along field lines toward the polar regions, giving rise to the aurora [5]. In laboratory plasmas such as reverse-field pinches, enhanced ion heating has been seen to correlate with magnetic fluctuations associated with reconnection and dynamo activity [6].…”
mentioning
confidence: 99%
“…caused by those reconnections and their mode cascades up to ion-gyromode number causes the anomalous ion heating [15]. Stenzel performed a famous laboratory experiment of magnetic reconnection using a discharge current between electrodes as a current-sheet.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…We have measured proton heating in MST with a five-channel charge-exchange analyzer (CXA) [26], and CV ion heating with a VUV spectrometer, both with fast time resolution (10 #s), and have found that the ion temperature exhibits rapid increases during discrete dynamo bursts [9,10] (Fig. 4) which are also periods of increased magnetic activity.…”
Section: Anomalous Ion Heatingmentioning
confidence: 99%
“…The Ohmic power input in the RFP is increased over that of a tokamak due to geometric effects and the dynamo [2,3,4,5], which may also supply the extra power drawn directly by ions in 'anomalous' heating [6,7,8,9,10]. As a result, an RFP " reactor may reach ignition with only Ohmic power input [11,12].…”
Section: Introductionmentioning
confidence: 99%